Personality organization and anxiety symptoms: Investigating the mediation of perfectionism - Krisztina Csáky-Pallavicini; Zsolt Horváth; Zsolt Unoka; Bernadette Kun; Zsolt Demetrovics (Comprehensive Psychiatry)
Background and aims: Personality functioning has increasing significance in the assessment of mental health and mental disorders. Otto Kernberg's model of personality organization is an extensively applied, theoretically grounded approach to categorizing the severity of personality impairment based on intrapsychic and interpersonal functioning. The Inventory of Personality Organization (IPO) self-report rating scale and its 16-item short version were developed to assess personality organization based on this model. This study aimed (i) to examine the factor structure of the short, 16-item version of the IPO, and (ii) to investigate the mediating effect of perfectionism on the relationship between personality organization and anxiety. Methods: 4340 individuals (mean age 37.7 years; 50.7 % females) were assessed for anxiety (Brief Symptom Inventory) and perfectionism (Multidimensional Perfectionism Scale) besides applying the 16-item IPO. Results: A bifactor model with three specific factors showed the most optimal levels of model fit for the IPO-16. Only the general personality dysfunction factor was characterized by high levels of internal reliability. Self-oriented and socially prescribed perfectionism mediated the relationship between the general personality dysfunction factor and anxiety symptoms. Higher levels of GPD predicted higher rates of self-oriented and socially prescribed perfectionism, which contributed to more severe symptoms of anxiety. Conclusion: The IPO-16 can be usefully applied to assess a general level of personality dysfunction both in research and in clinical use.